2021
DOI: 10.1371/journal.pone.0248218
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of dried blood spot (DBS) cards in antibody measurement: A systematic review

Abstract: Background Increasingly, vaccine efficacy studies are being recommended in low-and-middle-income countries (LMIC), yet often facilities are unavailable to take and store infant blood samples correctly. Dried blood spots (DBS), are useful for collecting blood from infants for diagnostic purposes, especially in low-income settings, as the amount of blood required is miniscule and no refrigeration is required. Little is known about their utility for antibody studies in children. This systematic review aims to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 58 publications
(395 reference statements)
0
45
1
Order By: Relevance
“…However, for prolonged storage, longer than 28 days, the systematic review by Amini et al . indicated that storage at -20°C is the optimal solution [ 23 ]. In g-iELISA, work is ongoing to overcome stability problems (short shelve life of 8 months on 2–8°C) with an impact on storage conditions and on looking for alternatives for filter paper to collect DBS as the number of discs required for testing is high [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for prolonged storage, longer than 28 days, the systematic review by Amini et al . indicated that storage at -20°C is the optimal solution [ 23 ]. In g-iELISA, work is ongoing to overcome stability problems (short shelve life of 8 months on 2–8°C) with an impact on storage conditions and on looking for alternatives for filter paper to collect DBS as the number of discs required for testing is high [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collecting capillary blood through dried blood spots (DBS) provide a more scalable alternative. DBS show comparable antibody measurements to serum samples for falciparum malaria, some bacterial and protozoal pathogens, and numerous viral pathogens, including vaccine-preventable diseases (63).…”
Section: Specimen Collection and Testingmentioning
confidence: 93%
“…DBS can be transported to remote sites for testing with more resource-intensive methods such as multiplex immunoassays. They can be kept at cool or ambient temperatures for several weeks before they are frozen for long-term storage (63), as long as high temperatures are avoided. Serum Separator cards can be used to automatically separate serum from DBS, further reducing the effort required to process these samples (64).…”
Section: Specimen Collection and Testingmentioning
confidence: 99%
“…In these circumstances, dried blood samples (DBS) could represent a convenient sample for antibody detection [13], being easy to collect, store and transport without cold chain [14]. DBS have been used in the surveillance and monitoring of numerous infectious diseases [13][14][15][16][17][18][19]. The good correlation between antibody concentrations in DBS and serum/plasma samples support the wider use of DBS in post-vaccination and seroepidemiological studies [13].…”
Section: Introductionmentioning
confidence: 99%